PENGARUH KONSELING KELOMPOK PENDEKATAN BEHAVIORAL DENGAN TEKNIK MODELING TERHADAP PENINGKATAN DISIPLIN BELAJAR SISWA - Bandel Ari Wijaya; Muhammad Japar; Nofi Nur Yuhenita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to examine the effect of behavioral approach group counseling with modeling techniques on improving student learning discipline. This research is animpure experimental research (Pre-experimental Design (non design)), with the experimental form of One-Group Pretest-Posttest Design. The sample of this study was selected by purposive sampling. The samples taken in this study were 5 students or teenagers as the experimental group. The method of data analysis was confirmed by using a disciplinary questionnaire in learning. Test the validity of the disciplinary questionnaire instrument in learning by using the product moment formula while the reliability test using the Cronbach alpha formula with the help of the SPSS For Windows version 24.00 program. The analysis prerequisite test consists of a normality test and a homogeneity test. Data analysis used parametric statistical techniques, namely the Paired Sample T-Test test with the help of the SPSS For Windows version 24.00 program.The results of this study indicate that behavioral group counseling Modeling techniques have an effect on increasing discipline in student learning. This is evidenced by the results of the paired sample t-test by showing the asymp probability. sig. (2-tailed) < 0.05 then H0 is rejected, Ha is accepted, whereas if the probability is asymp. Sig. (2-tailed)> 0.05 then H0 is accepted and Ha is rejected. In the table above, it can be seen the probability value of asymp. Sig. (2-tailed) <0.05 or 0.000 <0.05 or H0 is rejected and Ha is accepted, then according to the basis of decision making in the paired sample t-test, it can be concluded that there is a significant difference in the pretest and posttest scores in filling out the discipline questionnaire in learning, so that group counseling services with a behavioral approach to improve student learning discipline.